Modification of surfactant chemical structure for graphene/biopolymer conductive nanocomposites - Tretya Ardyani (Tanjong Malim, 2019)
Modification of surfactant chemical structure for graphene/biopolymer conductive nanocomposites by Tretya Ardyani